Are infrastructure development, economic complexity index, and oil cnsumption really matter for green economic recover? The role of institutions - Zhang, Haiying; Zhou, Wangxun (Frontiers in Environmental Science, 2023)
One of the most widely recognized tactics for ensuring long-term development at the national level, green economic growth approaches require the development of a nation to be implemented. The present study examines the effects of infrastructure development, oil consumption, and institution on carbon emission in the presence of economic complexity index, urbanization, infrastructure development, oil consumption, and institution quality in 30 provinces of China region from 2000 to 2020. This study employed second-generation panel cointegration methodologies. Similarly, the results of the CUP-FM & CUP-BC tests confirm the relationship between carbon emission and other variables used in this study. The estimation shows that the economic complexity index, urbanization, and oil consumption increase carbon emissions, whereas infrastructure development and institution have a significantly negative impact on carbon emissions. The robustness check findings obtained CUP-BC test validates the results. The study shows the moderate effect of institutions on the economic complexity index, urbanization, and infrastructure development has a negative impact on carbon emissions. In light of outcomes, the current study suggests decent policy implications to attain a green economic recovery.